Long-term course of orthostatic tremor in serial posturographic measurement. Issue 8 (August 2015) - Feil, K.; Böttcher, N.; Guri, F.; Krafczyk, S.; Schöberl, F.; Zwergal, A.; Strupp, M.
Abstract: Objective: Primary orthostatic tremor (OT) is a rare neurological disease of unknown pathophysiology characterized by a high-frequency tremor mainly of the legs when standing. The aim of this study was to examine its long-term course by subjective estimation and objective recording by serial posturography and to obtain further standardized epidemiological and clinical data on patients with OT. Methods: A clinical cohort of 37patients with the diagnosis of primary OT was screened for this longitudinal follow-up study. Eighteen patients consented to participate. During study visit all patients underwent a standardized neurological examination and completed subjective scales and scores. Posturographic recordings at follow-up were compared to prior clinical posturographic measurements in 15cases. Results: In our cohort the mean duration of symptoms was 14.1 ± 6.8 years. Subjectively, 78% of patients reported progression of the disease. Posturographic data (5.4 ± 4.0 years) revealed a significant increase of the total sway path (standing on firm ground with eyes open) from 2.4 ± 1.3 to 3.4 ± 1.4 m/min (p = 0.022) and of the total root mean square values from 9.8 ± 4.3 to 12.4 ± 4.8 mm (p = 0.028). None of these observations are explained by aging of the patients. Mean frequency of the tremor did not change over time (14.7 ± 1.9 Hz vs. 14.9 ± 2.0 Hz at follow-up). Clinically, most patients had signs of cerebellar dysfunction and a substantial portion also showed proprioceptive deficits in the long-term course. Conclusions: This long-term follow-up study indicates, that primary OT is a progressive disorder. Furthermore, the clinical observation of cerebellar dysfunction in most OT patients in the long-term course might indicate an important role of the cerebellum in its pathophysiology. Highlights: We examined patients with primary OT from a clinical cohort over time using serial posturographic measurements. All patients had a complete neurological, neuro-otological and neuro-ophthalmological examination. We showed an objective progression of disease by serial posturographic measurements which impacts seriously on quality of life. The changes shown are not age-related, but disease-related. The patients' subjective estimation also shows a progression of symptom severity over the course of disease.